Conceptual Correspondence Between the Rhetorical Qualities of Typographic Expressions Present in the Advertising Signs of a Particular Urban Area, and the Essential Cultural Components of That Environment Captured Through Visual Ethnography. a Case: Meiggs Neighborhood, in Santiago de Chile [Correspondencia Conceptual Entre Las Cualidades Retóricas de Las Expresiones Tipográficas Presentes en Los Rótulos Publicitarios de Una Determinada Zona Urbana y Los Componentes Culturales Esenciales de Dicho Entorno, Capturados a Través de la Etnografía Visual. Un Caso: Barrio Meiggs, en Santiago de Chile] - Osorio-Flores, R (Universidad de Caldas, 2021)
This is a qualitative research of an exploratory nature, which seeks to examine the conceptual correspondence between the rhetorical qualities of typographic expressions present in the advertising signs of a particular urban area and the essential cultural components of that environment, captured through visual ethnography. The case study was carried out in the Meiggs neighborhood, located in the city of Santiago de Chile. Through visual ethnography the sociocultural events of the neighborhood were captured through photographs. This led to a cataloging of the captures based on identification and description parameters which allowed grouping them based on descriptive matches. Ten groups were formed and a photo of each one was selected for the study. A connotative interpretation template was created for the analysis of the images which enabled to reach a conceptual synthesis based on referential and non-referential thematic descriptors. Each photograph was accompanied by a news story concerning the neighborhood and related to its specific content. Subsequently, the news stories were synthesized into concepts using a speech analysis software (part-of-speech.info) and, from there, it was possible to establish an essential concept of photography and its content. Then the typographic expression present in the labels was also subjected to the process of connotative interpretation and rhetorical analysis, managing to find in all the cases analyzed, a conceptual correspondence between the ethnographic images and the typographical expressions. Understanding that it is from, and in the public space where the urban landscape is articulated, and that the behaviors, actions, interactions, mobility and material and intangible symbolic manifestations of the people who inhabit that space are evidenced there, the typographic expressions in this case, those present in the advertising labels of the environment, emerge in that context as material representations of this sociocultural event, in this case from the Meiggs neighborhood. © 2021 Universidad de Caldas. All rights reserved.
Keywords: Culture; Meiggs; Neighborhood; Typography